1984
DOI: 10.1021/jm00369a033
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal antiinflammatory agents. 14. Synthesis and pharmacological profile of 6-chloro-5-(cyclopentylmethyl)indan-1-carboxylic acid

Abstract: The preparation of 6-chloro-5-(cyclopentylmethyl)indan-1-carboxylic acid is described. This acid has good anti-inflammatory and analgesic activities without producing irritation in the gastrointestinal tract up to the highest tested dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Therefore, there is an urgent need to develop new classes of therapeutic agents to treat microbial infections. Indanyl derivatives have already drawn some attention as one of the templates for synthesizing compounds of varying biological activities such as antimicrobial [1][2][3][4][5][6][7], antitubercular [8][9][10], antimalarial [11], anti-inflammatory [12][13][14][15][16], anticancer 1 [17,18], antiviral [19], monoamine oxidase inhibitor [20], and anti-Alzheimer [21]. In search of newer antimicrobial agents, I have discovered and evaluated a series of substituted indanyl acids [(5-ethoxy-6-methoxy-3-oxo-2,3-dihydro-1H-inden-l-yl)acetic acid, (5,6-dimethoxy-3-oxo-2,3-dihydro-1H-inden-l-yl) acetic acid, and (6-chloro-3-oxo -2, 3-dihydro-1H-inden-l-yl) acetic acid] and their esters [(5-ethoxy-6-methoxy-3-oxo-2,3-dihydro-1H-inden-lyl)acetic acid esters, (5,6-dimethoxy-3-oxo-2,3-dihydro-1H-inden-l-yl) acetic acid esters, and (6-chloro-3-oxo -2, 3-dihydro-1H-inden-l-yl) acetic acid esters] against various pathogenic microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is an urgent need to develop new classes of therapeutic agents to treat microbial infections. Indanyl derivatives have already drawn some attention as one of the templates for synthesizing compounds of varying biological activities such as antimicrobial [1][2][3][4][5][6][7], antitubercular [8][9][10], antimalarial [11], anti-inflammatory [12][13][14][15][16], anticancer 1 [17,18], antiviral [19], monoamine oxidase inhibitor [20], and anti-Alzheimer [21]. In search of newer antimicrobial agents, I have discovered and evaluated a series of substituted indanyl acids [(5-ethoxy-6-methoxy-3-oxo-2,3-dihydro-1H-inden-l-yl)acetic acid, (5,6-dimethoxy-3-oxo-2,3-dihydro-1H-inden-l-yl) acetic acid, and (6-chloro-3-oxo -2, 3-dihydro-1H-inden-l-yl) acetic acid] and their esters [(5-ethoxy-6-methoxy-3-oxo-2,3-dihydro-1H-inden-lyl)acetic acid esters, (5,6-dimethoxy-3-oxo-2,3-dihydro-1H-inden-l-yl) acetic acid esters, and (6-chloro-3-oxo -2, 3-dihydro-1H-inden-l-yl) acetic acid esters] against various pathogenic microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these compounds have eventually turned out to be pharmacologically active with any practical uses [1,4]. Many indan derivatives are indan acids, and they were synthesized as potential analgesic and anti-inflammatory agents [1,[5][6][7][8][9][10][11][12][13][14][15]. For example, the analogues of p-alkylphenylacetic acids and 5-alkyl-1-indan-carboxylic acids were synthesized as anti-inflammatory agents, and among them, 6-chloro-5-cyclohexyl-1-indancarboxylic acid was found to possess the highest level of analgesic, anti-inflammatory and antipyretic activities [16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the analogues of p-alkylphenylacetic acids and 5-alkyl-1-indan-carboxylic acids were synthesized as anti-inflammatory agents, and among them, 6-chloro-5-cyclohexyl-1-indancarboxylic acid was found to possess the highest level of analgesic, anti-inflammatory and antipyretic activities [16]. Later, 6-chloro-5-cyclohexyl-1-indancarboxylic acid was introduced into the market as Clidanac as an antiinflammatory drug ( Figure 1) [5,7,17]. However, this compound displayed significant ulcerogenicity along with anti-inflammatory activity at a dose of 400 mg/kg.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An isomer of Clidanac, 6-chloro-5-(cyclopentylmethyl)indan-1-carboxylic acid was also devoid of any mucosal damage in the rat stomach upto highest tested dose of 400 mg/kg. 6) It has been shown that the biochemical differences between the cyclooxygenase (COX) isoforms can be exploited to improve upon the selectivity of carboxyl containing nonsteroidal anti-inflammatory drugs (NSAIDs) as COX-2 inhibitors. Successful transformation of indomethacin and meclofenamic acid into selective COX-2 inhibitors by a single chemical derivatisation (amidation or esterification) has been reported.…”
mentioning
confidence: 99%